Carotid Flow Time Test Performance for the Detection of Dehydration in Children With Diarrhea. (9th November 2017) - Mackenzie, David C.; Nasrin, Sabiha; Atika, Bita; Modi, Payal; Alam, Nur H.; Levine, Adam C.
Abstract : Objectives: Unstructured clinical assessments of dehydration in children are inaccurate. Point‐of‐care ultrasound is a noninvasive diagnostic tool that can help evaluate the volume status; the corrected carotid artery flow time has been shown to predict volume depletion in adults. We sought to determine the ability of the corrected carotid artery flow time to identify dehydration in a population of children presenting with acute diarrhea in Dhaka, Bangladesh. Methods: Children presenting with acute diarrhea were recruited and rehydrated according to hospital protocols. The corrected carotid artery flow time was measured at the time of presentation. The percentage of weight change with rehydration was used to categorize each child's dehydration as severe (>9%), some (3%–9%), or none (<3%). A receiver operating characteristic curve was constructed to test the performance of the corrected carotid artery flow time for detecting severe dehydration. Linear regression was used to model the relationship between the corrected carotid artery flow time and percentage of dehydration. Results: A total of 350 children (0–60 months) were enrolled. The mean corrected carotid artery flow time was 326 milliseconds (interquartile range, 295–351 milliseconds). The area under the receiver operating characteristic curve for the detection of severe dehydration was 0.51 (95% confidence interval, 0.42, 0.61). Linear regression modeling showed a weak association between the flow time and dehydration. Conclusions: The corrected carotid artery flow time was a poor predictor of severe dehydration in this population of children with diarrhea.